Design and fabrication of POF/PCF based optical switch for Local Area Network (LAN) system - Bhuiyan, Moinul; Ahmed, Sayem (2014)
The polymer optical fiber (POF) is mostly suitable for house held optical switches because of its large core diameter. A high performance optical switch building process is described in this paper. In order to achieve high performance switching and low data loss, we examine different technique while building different parts. Furthermore, we show the comparison of surface roughness of POF/PCF using different processing methodology to minimize the optical insertion loss. This research developed a fiber fixing Jig for Mechanical polishing method,and we discovered that, the Mechanical polishing method able to provide 1/3 (0.08dB) optical insertion loss than the Mechanical cutting method. Another challenge was to build the main structure of the switch, and how to Seal inside’s matching oil properly. As long as, our target is to build a low-cost switch, we selected an acrylic substrate for the body.